The neuroprotective effect of dexmedetomidine and its mechanism - Hu, Yijun; Zhou, Hong; Zhang, Huanxin; Sui, Yunlong; Zhang, Zhen; Zou, Yuntao; Li, Kunquan; Zhao, Yunyi; Xie, Jiangbo; Zhang, Lunzhong (Frontiers in Pharmacology, 2022)
Dexmedetomidine (DEX) is a highly selective α2 receptor agonist that is routinely used in the clinic for sedation and anesthesia. Recently, an increasing number of studies have shown that DEX has a protective effect against brain injury caused by traumatic brain injury (TBI), subarachnoid hemorrhage (SAH), cerebral ischemia and ischemia–reperfusion (I/R), suggesting its potential as a neuroprotective agent. Here, we summarized the neuroprotective effects of DEX in several models of neurological damage and examined its mechanism based on the current literature. Ultimately, we found that the neuroprotective effect of DEX mainly involved inhibition of inflammatory reactions, reduction of apoptosis and autophagy, and protection of the blood–brain barrier and enhancement of stable cell structures in five way. Therefore, DEX can provide a crucial advantage in neurological recovery for patients with brain injury. The purpose of this study was to further clarify the neuroprotective mechanisms of DEX therefore suggesting its potential in the clinical management of the neurological injuries.